2020
DOI: 10.3389/fped.2020.618119
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Balance in Pediatric Acute Liver Failure: Epidemiology of Bleeding and Thrombosis, Physiology, and Current Strategies

Abstract: Pediatric Acute Liver Failure (PALF) is a rapidly progressive clinical syndrome encountered in the pediatric ICU which may rapidly progress to multi-organ dysfunction, and on occasion to life threatening cerebral edema and hemorrhage. Pediatric Acute Liver Failure is defined as severe acute hepatic dysfunction accompanied by encephalopathy and liver-based coagulopathy defined as prolongation of International Normalized Ratio (INR) >1.5. However, coagulopathy in PALF is complex and warrants a deeper unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
(86 reference statements)
1
19
0
Order By: Relevance
“…All coagulation factors are markedly decreased during the synthetic functional deficiency of the liver parenchyma during fulminant liver failure. [26] Our results also showed that all parameters of the conventional coagulation tests in the ALF group were abnormally reduced or prolonged. Most measurements of ROTEM ® in the ALF group were out of the reference range [20] (55% for increased INTEM CT, 85% for increased INTEM CFT, and 63% for decreased EXTEM MCF).…”
Section: Discussionsupporting
confidence: 69%
“…All coagulation factors are markedly decreased during the synthetic functional deficiency of the liver parenchyma during fulminant liver failure. [26] Our results also showed that all parameters of the conventional coagulation tests in the ALF group were abnormally reduced or prolonged. Most measurements of ROTEM ® in the ALF group were out of the reference range [20] (55% for increased INTEM CT, 85% for increased INTEM CFT, and 63% for decreased EXTEM MCF).…”
Section: Discussionsupporting
confidence: 69%
“…Liver failure leads to a decrease in hepatic synthetic coagulation factors, hyperfibrinolysis, and thrombocytopenia caused by hypersplenism[ 27 , 28 ]. Therefore, patients with liver failure have always been considered to be in a low coagulation state [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…If acute liver failure (ALF) occurs, various factors, such as decreased coagulation factor synthesis, decreased hepatic thrombopoietin, and secondary bacterial infection, may lead to coagulation disorders [ 26 ]. Prothrombin activity (PTA) and INR can be used to evaluate coagulation function in clinical practice.…”
Section: Treatmentmentioning
confidence: 99%